Comparison of Columnar, Surface, and UAS Profiles of Absorbing Aerosol Optical Depth and Single-Scattering Albedo in South-East Poland - Michał T. Chiliński; Krzysztof M. Markowicz; Olga Zawadzka; Iwona S. Stachlewska; Justyna Lisok; Przemysław Makuch (Atmosphere, 2019)
The impact of absorbing aerosols on climate is complex, with their potential positive or negative forcing, depending on many factors, including their height distribution and reflective properties of the underlying background. Measurement data is very limited, due to insufficient remote sensing methods dedicated to the retrieval of their vertical distribution. Columnar values of absorbing aerosol optical depth (AAOD) and single scattering albedo (SSA) are retrieved by the Aerosol Robotic Network (AERONET). However, the number of available results is low due to sky condition and aerosol optical depth (AOD) limitation. Presented research describes results of field campaigns in Strzyżów (South-East Poland, Eastern Europe) dedicated to the comparison of the absorption coefficient and SSA measurements performed with on-ground in-situ devices (aethalomter, nephelometer), small unmanned aerial system (UAS) carrying micro-aethalometer, as well as with lidar/ceilometer. An important aspect is the comparison of measurement results with those delivered by AERONET. Correlation of absorption to scattering coefficients measured on ground (0.79) and correlation of extinction on ground to AOD measured by AERONET (0.77) was visibly higher than correlation between AOD and AAOD retrieved by AERONET (0.56). Columnar SSA was weakly correlated with ground SSA (higher values of columnar SSA), which were mainly explained by hygroscopic effects, increasing scattering coefficient in ambient (wet conditions), and partly high uncertainty of SSA retrieval. AAOD derived with the use of profiles from UAS up to PBL height, was estimated to contribute in average to 37% of the total AAOD. A method of AAOD estimation, in the whole troposphere, with use of measured vertical profiles of absorption coefficient and extinction coefficient profiles from lidars was proposed. AAOD measured with this method has poor correlation with AERONET data, however for some measurements, within PBL, AAOD was higher than reported by AERONET, suggesting potential ...